2017
DOI: 10.1038/s41598-017-05801-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs with prognostic significance in bladder cancer: a systematic review and meta-analysis

Abstract: The aim of this study was to systematically review articles that investigated the prognostic significance of different microRNAs in bladder cancer (BC). We systematically searched PubMed, Web of Science, and Embase to identify relevant studies until March 2016. After screening, 26 studies that involved 2753 patients were included. Results suggested that many miRs expression aberration may predict prognosis in patients with BC. There are six miRs (miR-21, miR-143, miR-155, miR-200, miR-214, and miR-222) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 73 publications
2
35
1
Order By: Relevance
“…Concerning clinical significance, there are controversial results with some studies showing that miR‐100 downregulation is associated with unfavorable prognosis . Nevertheless, other studies, which are in line with our result, indicate that miR‐100 downregulation is associated with a better outcome .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Concerning clinical significance, there are controversial results with some studies showing that miR‐100 downregulation is associated with unfavorable prognosis . Nevertheless, other studies, which are in line with our result, indicate that miR‐100 downregulation is associated with a better outcome .…”
Section: Discussionsupporting
confidence: 79%
“…Recent data suggest that microRNA profiles can distinguish between different histological types, and separate them in different grade and stage categories . Thus, there is strong interest in finding microRNA activity‐based biomarkers since they might provide insights regarding which patient may have a better prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of miRNA-143 in bladder cancer correlate with clinical stage, lymph node metastasis, distant metastasis, and prognosis Despite high levels of miRNA-143 correlating with poor progression-free survival in aggressive bladder cancer [174] this miRNA has been shown to enhance sensitivity to gemcitabine in 5637 cells; this was proposed to be via repression of IGF-1R signaling Further to this, in vitro experiments which induced FOXD2-AS1 knockdown, a long non-coding RNA which can inhibit miRNA-143, enhanced sensitivity to gemcitabine [175].…”
Section: Increased Levels Of Mirna-143 Enhance Chemosensitivity In Blmentioning
confidence: 99%
“…It has been reported that miR-21 is overexpressed in multiple human solid tumors, including bladder cancer (5,6). A systematic review and meta-analysis showed that elevated miR-21 expression is associated with poor overall survival and proposed that miR-21 may serve as follow-up marker for early detection of bladder cancer progression or recurrence (7). Furthermore, miR-21:miR-205 ratio has been described as a tool for identifying the invasive capacity of bladder tumors with high sensitivity and specificity (6).…”
Section: Introductionmentioning
confidence: 99%